2018
DOI: 10.1038/s41391-018-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of DNA repair gene mutations in localized prostate cancer according to clinical and pathologic features: association of Gleason score and tumor stage

Abstract: The prevalence of pathogenic DNA repair gene alterations is enriched in men with advanced tumor stages and higher Gleason grade groups, with maximal enrichment observed in those with Gleason grade group ≥ 3 and clinical stage ≥ cT3 disease. This information can be used to guide eligibility criteria for genomically targeted clinical trials in the neoadjuvant/adjuvant settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 23 publications
6
55
2
3
Order By: Relevance
“…The observed DDR pathway alterations rate in localized prostate cancer was significantly higher than expected based on the reported range of 8-20% [8,9]. Previously, DDR pathway has been reported to be altered in the 30% range in men with mCRPC.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The observed DDR pathway alterations rate in localized prostate cancer was significantly higher than expected based on the reported range of 8-20% [8,9]. Previously, DDR pathway has been reported to be altered in the 30% range in men with mCRPC.…”
Section: Discussioncontrasting
confidence: 57%
“…To test this possibility we are currently designing an adjuvant trial that will assess the effect of a PARP inhibitor in prostate cancer patients with high-risk features post-operatively. It should be noted that a recent manuscript also investigated the DDR pathway in localized prostate cancer using the same TCGA database [9]. However, there were two significant differences between the present and the aforementioned study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In our case, the Gleason grade group was 5, with an expected poor prognosis. A previous study reported that the prevalence of DNA repair mutation involving FANCA was higher in prostate cancer cases with high Gleason grade groups than in cases with low Gleason grade groups [16].…”
Section: Discussionmentioning
confidence: 90%
“…Homologous repair deficiency (HRD) genes (particularly BRCA1/2) are found in 20-25% of all patients with metastatic CRPC [11]. Although the 2019 National Comprehensive Cancer Network guidelines recommend germline testing for all prostate cancer patients, treatment based on molecular characterization is still not commonly practiced [8].…”
Section: Discussion/conclusionmentioning
confidence: 99%